FACTORS AFFECTING THE COMPETITIVE ADVANTAGE OF CONSTRUCTION COMPANIES IN INDONESIA - Novi Sudiansyah; Tri Joko Wahyu Adi (Jurusan Arsitektur - FTSP - Universitas Trisakti, 2022)
Competitive advantage is an important factor in the success of construction companies in a competitive market. To achieve a competitive advantage, construction companies must understand the factors that influence it and implement the right strategy. This study aims to analyze the factors that influence the competitive advantage of construction companies in Indonesia. It is an exploratory research. Factors affecting competitive advantage were obtained from an in-depth literature review and structured interviews with leaders of Indonesian state-owned construction companies. The results were then analyzed using the Relative Important Index (RII). The results highlight three main factors affecting the competitive advantage of construction companies in Indonesia: company characteristics, technology adoption, and technology readiness. Implementing the outputs of this research can be beneficial for companies to face intense global competition, by taking strategic steps to improve their competitive advantage in the construction industry.